Assessment of Dental Prosthetic Status and Needs Among Prisoners of Haryana, India - Bansal, Vikram; Veeresha, K. L.; Sogi, G. M.; Kumar, Adarsh; Bansal, Shelly (The journal of Indian Prosthodontic Society, 2013)
This cross-sectional study was planned to evaluate the prosthetic status and treatment needs using WHO (1997) format among prisoners of Haryana state, India. 1,393 subjects with age range of 35.26 ± 12.29 years were examined. Of the study subjects, 11 (0.8 %) were completely while 606 (43.5 %) were partially edentulous. Of these 617 subjects, 305 (49.4 %) were edentulous only in posterior region. Dental caries accounted for loss of teeth in 325 (52.7 %) subjects. 44 (7.1 %) subjects were wearing some prosthesis. Regarding dental arch wise prosthetic need, 335 (54.3 %) subjects needed prosthesis in maxillary arch while 482 (78.1 %) needed prosthesis in mandibular arch. With advancing age there was an increase in the number of complete dental prosthesis required. There was no statistically significant difference between length of imprisonment and prosthetic need, except for need of a combination of prosthesis. Only one-fourth of the prisons had a dentist. The prisoners were taken to a hospital outside the prison in case of health needs. Prosthetic needs of prisoners were high. The lack of dental infrastructure in prisons makes the provision for multi-visit conservative dental treatments very difficult leading to higher tooth mortality. People who migrate back and forth across the prisons and communities represent a public health opportunity that should be addressed.